[PP.01.18] ARE WE LOOKING IN THE RIGHT DIRECTION FOR BLOOD PRESSURE CONTROL?. (September 2017) - Tilea, I.; Varga, A.; Morar, S.I.; Tatar, C.M.; Bocicor, A.E.
Abstract : Objective: The efficiency of antihypertensive treatment of free versus fixed combination and blood pressure control was assessed together with the number of antihypertensive classes used for on target blood pressure (BP) control in real life practice of adult population. Design and method: An observational retrospective study was performed on a cohort of 484 adult hypertensive patients (mean age 62.06 ± 12.30 y.o.) from an urban Family Practice, over 3 years (2011–2014). History of hypertension was recognized by at least 1 year. Subjects were classified by the number of antihypertensive classes (6) and a fixed combination (sartan and calcium channel blocker in variable doses) used. Relationship between BP control and age, sex, education and area of origin was also studied. Results: Statistical analysis of pooled data showed a usage of 3 classes of antihypertensive drugs in 36.2% hypertensive patients in long-term treatment. One or two classes of antihypertensive drugs were used in 44.8% of the patients and 5.6% had a non-pharmacological approach. 173 hypertensive patients have been identified using fixed combination therapy. This administration has demonstrated its benefit in achieving target BP with no statistical significance, 81 patients had uncontrolled BP, versus 92 patients with controlled BP (p value = 0.40). Non-pharmacological treatment alone was found 9.9% (48 pts) in 2011 for 2014 to be used in 27 individuals (5.6%); 9 hypertensive patients (33.33%) achieved the target values of BP. A statistically significant difference among patients with target BP considering the number of antihypertensive classes used (p = 0.04) was demonstrated. 35.4% patients with controlled BP were using 3 classes of antihypertensive drugs. Regarding the BP control reported to studied demographic data we did not identify statistically significant differences for systolic BP (SBP) and diastolic BP (DBP) in our particular hypertensive population of 41% of patients with high-level education. Conclusions: Concomitant use of three antihypertensive classes ensures a better control of both SBP and DBP in our real life practice hypertensive population studied. As a future strategy for BP target control, a better education level should be promoted with long-term reduction on CV outcomes and positive impact on healthcare expenses.